Are the Stock Exchanges of Emerging Economies Interlinked?: Evidence from BRICS - Sharma, Gagan Deep; Mahendru, Mandeep; Singh, Sanjeet (Indian Journal of Finance, 2013)
This paper studies the interlinkages between stock markets of Brazil, Russia, India, China and South Africa (BRICS) with the help of benchmark indices of these stock exchanges. Daily closing levels of the benchmark indices in the five countries were taken for a period from April 1, 2005 to March 31, 2010. Line charts and unit-root tests were applied to check the stationary nature of the series; Regression Analysis, Granger's Causality Model, Vector Auto Regression (VAR) Model, and Variance Decomposition Analysis were performed to find out the linkages between the markets under study. The analysis revealed that the stock markets under study were influenced by each other, but not to a great extent. It implies that there exists opportunities for diversification of the investors among the stock exchanges of BRICS. The paper also observed that there are domestic factors (macro-economic variables) that influence the stock markets.